Renewable based distributed generation in Uganda: Resource potential and status of exploitation - Ssennoga, Twaha; MakbulA.M., Ramli; Patrick M., Murphy; Muhammad U., Mukhtiar; Nsamba, Hussein K. (Renewable and Sustainable Energy Reviews, 2016)
Uganda is gifted by nature with abundant energy resources, mainly renewables, which can potentially provide the country with sufficient capacity to meet future growth in energy demand. Surprisingly, Uganda has one of the lowest electricity penetration levels, with only 9–12% of the total population having electricity access;2–3% of them living in rural communities. There is multitude of challenges facing the energy sector of Uganda, forcing energy demand to always exceed the supply. For decades, hydro power has been and is still the base electricity supply of the country with a supplement of limited biomass, diesel based thermal and solar electricity. The objective of this paper is to review the potential and progress of renewable based distributed generation in Uganda. The potential of the country’s natural renewable resources and existing distributed generation is described and existing government policies are assessed.The challenges facing the energy sector and the suggested remedies are discussed.Various distributed generation systems that could be incorporated into the energy system of the country to improve renewable energy(RE) utilization and possibly contribute to the electricity needs of the population are also proposed and discussed. Exploitation of abundant RE resources through distributed energy generation around the region will not only improve the electricity needs of the country but also increase the economic welfare of the growing population.
Keywords: Solar; Hydro; Wind; Biomass